A comparison of two measures of explosive power - Igna, I.; Wygand, J.; Otto, R. M. (Medicine & Science in Sports & Exercise, 1996)
The standard vertical jump was compared to an experimental method of testing explosive power. The experimental method required jumping onto a raised platform. Time of flight was the variable measured. Significant differences existed between the two measures. Knee-joint angle did not effect performance on either test. It was suggested that flight time might be a more realistic measure of explosive power while being moderately correlated to the vertical jump. Implication. How explosive power is measured will partly determine the type of results obtained. It is incorrect to assume that all measures of explosive power measure the same capacity.